'Nonagon infinity opens the door!': Formation of a cross-album concept through motivic interrelation in the music of King Gizzard and the Lizard Wizard. (3rd July 2020) - Ballam-Cross, Paul
Abstract : The re-use of motifs is relatively common as a method of structuring concept albums. These motifs can appear in several different formats, but generally are musical or lyrical references that serve to generate a sense of cohesion across a release. Australian band King Gizzard and the Lizard Wizard have created what is referred to as the 'Gizzverse'—a collection of musical, lyrical and extra-musical motifs that are referenced across several releases. Their extensive re-use of motifs, discussed using Gérard Genette's frameworks for understanding multi-textual references, or transtextuality, creates an interconnected mythology that this article argues ultimately constitutes a kind of uber-concept album.